Longing for the Past: Nostalgic Elements in Kamala Das's Selected Poetry (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This research paper examines the pervasive theme of nostalgia in Kamala Das's poetry, focusing on four seminal works: "A Hot Noon in Malabar," "My Grandmother's House," "The Old Playhouse," and "My Mother at Sixty-six." Through close textual analysis, this study explores how Das employs nostalgic elements to articulate themes of loss, displacement, feminine identity, and the inexorable passage of time. The paper argues that nostalgia in Das's work functions not merely as sentimental longing but as a complex literary device that interrogates the relationship between memory, identity, and belonging. Drawing upon theoretical frameworks of nostalgia studies and feminist literary criticism, this research demonstrates how Das's nostalgic discourse reveals deeper anxieties about cultural dislocation, gender roles, and the erosion of traditional familial structures in post-colonial India. The findings suggest that Das's nostalgic poetry serves as both personal catharsis and cultural commentary, offering insights into the broader experience of women navigating modernity while mourning the loss of protective, nurturing spaces of the past.